DRAG AS RESISTANCE: GENDER PERFORMATIVITY AND THE SUBVERSION OF HETERONORMATIVITY IN HURRICANE BIANCA (2016) - Juana Handayani Suryanto; Maya Sekartaji (Prodi Sastra Inggris UKI, 2026)
In this research paper, the representation of gender performativity in Hurricane Bianca (2016) film will be analyzed from the point of view of how drag helps construct and resist identities in an institutional context dominated by heteronormativity. Through qualitative textual and visual analysis, Judith Butler’s concepts of gender performativity, citationality and iterability will be applied to examine how drag serves as both an arena for constructing gendered identities and a form of resistance to the institutional power of heteronormativity. Findings indicate that the gender identity of the drag queen Bianca Del Rio is neither essential nor fixed since it is created through multiple performative acts such as dressing, speaking, gesturing and naming oneself that cannot be explained by means of an essentialist concept of gender. Her resistance is performed through citationality, professionalism and taking up spaces in an institution, which allows her to deconstruct the heteronormative power that had previously excluded her and create a new definition of her position in the school's organizational structure. The current research paper reveals that Hurricane Bianca operates as a cultural text that uses drag as a political resistance act while pointing out the fragility of heteronormative conventions and their dependency on constant repetition